Farelo de canola na dieta de frangos de corte: desempenho, qualidade de carcaça e de carne - Gopinger, Edenilse (2013)
Canola meal has been studied as an alternative protein source to soybean meal in diets for non-ruminants. Therefore, this study aimed to evaluate the effects of different levels of canola meal in broiler diets on growth performance, carcass traits, digestibility, chemical composition of meat, meat quality (sensory and instrumental) and duodenal morphometry. Three hundred and twenty broilers, Cobb strain, were housed with one day old until 35 days, and were allotted to a completely randomized design with five levels of canola meal (T1 - 0%, T2 - 10%, T3 - 20%, T4 - 30% and T5 - 40%) in place of meal soybeans, and eight replicates of eight birds each. The basal diets were formulated based on corn and soybean meal, meeting the requirements of the birds. To evaluate the effect of inclusion levels of canola, except in sensory analysis, was used polynomial regression analysis. Sensory analysis was applied to analysis of variance and means were compared by Tukey test. In general the variables of weight gain and the average weight of the birds had a quadratic behavior in the different age groups and decreased with the addition of 40% canola meal. Increased levels of canola meal promoted a linear decrease in the yield of the chest at 35 days of age. The apparent digestibility of dry matter, crude protein and non-extractive nitrogen decreased linearly with increasing inclusion of canola meal. The chemical composition of the leg was not affected, but the chest was an increase in dry matter, ether extract increased and decreased moisture and ash with increasing levels of canola meal. With the inclusion of canola decreased intensity of yellow color of the meat. In sensory evaluation the only difference was found for the residual flavor of meat in 30% level of inclusion. In intestinal morphology was observed a quadratic effect unbeliever until the 20% level of inclusion of canola meal in the diet for villi height. In conclusion canola meal can be included into 20% in the diet of broilers without affecting any of the variables of interest husbandry.